Approaching to an optimal value of rise time in n-well/p substrate photodiode by controlling depletion layer width - Emad Hameed Hussein (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The relationship between response speed of a silicon n-well/p substrate photodiode and the depletion layer width has been investigated. Variation of both the junction capacitance and the series resistance of the photodiode with the depletion layer width have been analyzed. It is shown that the contribution of the time constant and the drift time in the rise time within the depletion layer can be decreased to an optimal value (less than 1ns) just for specific value of the depletion layer width and smaller value of the diffused junction area.